Edukasi Gemar Makan Sayur Strategi Penanggulangan Kelompok Risiko Stunting di Daerah Pesisir - Riry, Roberth Berthy; Berhitu, Petrus; Juwita, Hawina; Wattimena, Elona (Universitas Pattimura, 2023)
The Covid-19 case has entered an endemic phase since 2022, since then stunting cases have been widely discussed by many people, especially mothers. WHO defines stunting as a disorder of child growth and development caused by lack of nutritional intake, infection, or inadequate stimulation. In this situation, education on healthy behavior change with a risk communication approach needs to be applied both in prevention, treatment, and at the stage of rehabilitation of risk environments in island communities (coastal and small islands). This education aims to increase public knowledge of the potential risks and threats of health problems. Thus, they are able to determine the right steps and actions to protect themselves from these problems. The method used is the Base Learning Project (PBL) with preparation, action, and closing scenarios. The results of educational activities are the screening of animated videos on eating vegetables and fruits, presentations with material on eating vegetables, as well as vegetable gardening with hydroponics, practicing making hydroponic installations and planting vegetables and fruits.